Sosialisasi Pencegahan Stunting Sebagai Upaya Pemberdayaan Masyarakat - Muh. Jaelani Al-Pansori; Rian Ardianto; Dewi Lestari; Nurul Wahyuni Mahmud; Tia Rohliana; Aina Filhiam; Yazid Ilham Dia Uddin (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
Stunting is a serious nutritional issue in Indonesia that has the potential to hinder children's growth and development. This article discusses the role of students participating in the Community Service Program (KKN) in promoting stunting prevention in South Masbagik Village. Through the KKN activities, students collaborate with the local community to raise awareness about the importance of balanced nutrition and healthy lifestyles. The methods used include counseling and training. The results of these activities show an increase in the community's knowledge about stunting and its prevention measures. Additionally, this program has contributed to community empowerment by involving them in the decision-making process related to family health. Through the active role of students, it is hoped that awareness and preventive actions against stunting can be effectively implemented, leading to a positive impact on children's health and the quality of human resources in the village.